Cyclin-Dependent Kinase Inhibitor p21WAF1/CIP1 Facilitates the Development of Cardiac Hypertrophy - Yang-Fei Tong (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Adult cardiomyocytes can re-enter cell cycle as stimulated by prohypertrophic factors although they withdraw from cell cycle soon after birth. p21WAF1/CIP1, a cyclin-dependent kinase inhibitor, has been implicated in cardiac hypertrophy, however, its precise contribution to this process remains largely unclear. Methods: The gene expression profile in left ventricle (LV) of spontaneously hypertensive rats (SHR) and Wistar–Kyoto (WKY) rats was determined using quantitative PCR array and verified by real-time PCR and Western blotting. Hypertrophic response of H9c2 cells and neonatal rat ventricular myocytes (NRVM) were induced by angiotensin II (1 µmol/L). Cardiac hypertrophy of mice was elicited by isoproterenol (ISO) infusion (40 mg/kg per day for 14 days). p21-adenovirus and p21-siRNA were employed to transfect NRVM, and sterigmatocystin (STE, 3 mg/kg, ip, qd) was used to inhibit p21 activity. mRNA and protein expression levels of α- and β-myosin heavy chain (MHC), p21WAF1/CIP1, calcineurin (CaN) and atrial natriuretic peptide (ANP) were assayed by realtime PCR and WB, respectively. Results: Sixteen genes showed two-fold or greater changes between SHR and WKY rats, in which the expression of p21WAF1/CIP1 was upregulated by 4.15-fold (P=0.002) and reversed by losartan. Surface area, protein content, mRNA and protein expressions of β-MHC, ANP and p21WAF1/CIP1 in H9c2 cells treated with AngII elevated significantly compared with control group. p21-Ad transfection markedly increased the surface area and β-MHC mRNA expression of normal NRVMs, and p21-siRNA transfection decreased them in AngII-treated NRVMs. STE treatment decreased HW/BW and cross-sectional area, expression levels of β-MHC, ANP and p21 significantly in ISO-treated mice. Conclusion: Our findings suggest that p21 facilitates the development of cardiac hypertrophy, and regulating the expression of p21 may be an approach to attenuate hypertrophic growth of cardiomyocytes.